TASK-BASED INSTRUCTION IN THE ENGLISH LANGUAGE CONTEXT AND ITS SIGNIFICANCE FOR LESSON PLANNING - Orazbek Makhpal; Kudaibergenova M.R (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
What is task-based learning? Or should that be ‘task-based language teaching’? How do you use it in a lesson? What’s the difference between this and project-based learning? Read on! Task-Based Learning (TBL) is a lesson structure, a method of sequencing activities in your lessons. Sometimes called ‘task-based language teaching’, in TBL lessons, students solve a task that involves an authentic use of language rather than complete simple questions about grammar or vocabulary. Task-based learning is an excellent way to get students engaged and using English. That, plus the collaborative element, builds confidence in the language and social situations. It’s also been shown to align with how we learn a language.